การศึกษาความเป็นไปได้ของการสร้างสถานีบริการนํ้ามัน : กรณีศึกษา ศูนย์กลาง มหาวิทยาลัยเทคโนโลยีราชมงคลอีสาน The Feasibility Study of a Gasoline Station Construction : A Case Study of Rajamangala University of Technology Isan Nakornratchasima - ศรีศิลา, เฉลิมเกียรติ (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2015)
บทคัดย่อ งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาความเป็นไปได้ของการสร้างสถานีบริการนํ้ามัน กรณีศึกษา ศูนย์กลางมหาวิทยาลัยเทคโนโลยีราชมงคลอีสาน เพื่อลดความเสี่ยงหากมีการดำเนินงานและเป็นข้อมูลสำหรับผู้บริหารใช้พิจารณาและตัดสินใจเกี่ยวกับการจัดสร้างสถานีบริการนํ้ามันขึ้นภายในมหาวิทยาลัยฯ ขั้นตอนการศึกษาความเป็นไปได้ของโครงการแบ่งออกเป็น 2 ส่วน คือ ส่วนแรกเป็นการเก็บรวบรวมข้อมูลเพื่อนำมาใช้วิเคราะห์ด้านการตลาด ด้านการบริหาร และด้านวิศวกรรม สำหรับส่วนที่สองเป็นการวิเคราะห์ข้อมูลด้วยการศึกษาความเป็นไปได้ด้านการเงินและด้านเศรษฐศาสตร์ ใช้ดัชนีชี้วัดคือมูลค่าปัจจุบันสุทธิ (NPV) และอัตราผลตอบแทนภายใน (IRR) เป็นดัชนีชี้วัดประสิทธิภาพ ผลการศึกษาความเป็นไปได้ของโครงการเมื่อพิจารณาผลตอบแทนจากการลงทุน ณ ระดับอัตราดอกเบี้ย 4% และอายุโครงการเท่ากับ 20 ปี พบว่าโครงการต้องการเงินลงทุนเบื้องต้นทั้งหมด 10,843,059 บาท มีมูลค่าปัจจุบันสุทธิเท่ากับ 4,111,888 บาท และอัตราผลตอบแทนภายในเท่ากับ 5.92% สรุปโครงการสร้างสถานีบริการนํ้ามัน มีความเหมาะสมต่อการลงทุน Abstract The objective of this project is to conduct a feasibility study on a gasoline station construction in Rajamangala University of Technology, Nakornratchasima in order to reduce investment risks and also provide right information for the university executives in making decision. The study was divided into two main parts. Firstly, all relevant data were collected and the feasibility on marketing, management and engineering was investigated. Secondly, impacts on finance and economy were analyzed using Net Present Value (NPV) and Internal Rate of Return (IRR) as the key performance indicators. The result revealed that at 4% interest rate of investment within 20 years, the cost for the project of gasoline station construction should be 10,843,059 baht with Net Present Value (NPV) at 4,111,888 baht and Internal Rate of Return (IRR) at 5.92%. Thus, the investment on the gasoline station construction is recommended.